INSPEKSI TEKNIK INSTALASI FLARE STACK INDUSTRI MIGAS DAN LANJUTNYA - Sulardi Sulardi (PETROGAS: Journal of Energy and Technology, 2021)
Flare stack is a fire tower installation to burn off-specification gas that is not processed perfectly in the oil and gas processing or or in the petrochemical process. The purpose of this study is to provide a technical description of the condition of the flare stack installation in the refinery industry after being used for 40 years. The research method used is a technical inspection method with limited testing and inspection with a case study approach to problems in the flare stack installation. The results show that the building under the flare stack installation has experienced material degradation in the form of carbonation of the concrete structure to a depth of 5.5 millimeters and causes the concrete to become brittle. The results of the study recommend that it is necessary to immediately relocate and replace the existing flare installation because its estimated life span is 2 years. The results also recommend that the location that is considered suitable and suitable for flare stack installation is in the Balikpapan Bay area in the form of an offshore flare platform.